W kwestii kontaktów słowiańsko-skandynawskich we wczesnym średniowieczu. Wolińskie osełki z metalowymi zawieszkami - Janowski, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The article presents the origin and function of phyllite whetstones with ferrules. Some researchers trace them back to the inhabitants of Scandinavia. However, in the light of the available data and new findings, the whetstones should be attributed to Slavic craftsmen who may have operated in Wolin island. These whetstones were status symbols rather than daily use objects.